2012
DOI: 10.1021/jf300634k
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Apoptotic Potential of T-2 Toxin Metabolites in Human Cells

Abstract: The mycotoxin T-2 toxin, produced by various Fusarium species, is a widespread contaminant of grain and grain products. Knowledge about its toxicity and metabolism in the human body is crucial for any risk assessment as T-2 toxin can be detected in processed and unprocessed food samples. Cell culture studies using cells of human origin represent a potent model system to study the metabolic fate of T-2 toxin as well as the cytotoxicity in vitro. In this study the metabolism of T-2 toxin was analyzed in a cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…No HT-2 toxin was detectable after incubations with T-2 toxin, while this conversion is well described in literature for various cell types in vitro : primary cells of different human origin like RPTEC (kidney), NHA (astrocytes), NHLF (lung fibroblasts) as well as cell lines derived from human colon carcinoma cells (HT-29) metabolize T-2 toxin rapidly to HT-2 toxin [10], [11]. Metabolism studies mimicking the human gastrointestinal tract found also HT-2 toxin as the main or even sole metabolite after T-2 toxin application [25].…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…No HT-2 toxin was detectable after incubations with T-2 toxin, while this conversion is well described in literature for various cell types in vitro : primary cells of different human origin like RPTEC (kidney), NHA (astrocytes), NHLF (lung fibroblasts) as well as cell lines derived from human colon carcinoma cells (HT-29) metabolize T-2 toxin rapidly to HT-2 toxin [10], [11]. Metabolism studies mimicking the human gastrointestinal tract found also HT-2 toxin as the main or even sole metabolite after T-2 toxin application [25].…”
Section: Resultsmentioning
confidence: 52%
“…Concerning the toxicity, T-2 and HT-2 toxin exhibit similar toxic properties: caspase-3-activation and subG1 formation as indicators of apoptosis were observed in primary human kidney cells for both toxins in similar concentration ranges [10], 11. Moreover, T-2 toxin is a well described inhibitor of eukaryotic protein synthesis.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several older in vivo and in vitro studies in animals provide indirect evidence for the formation of glucuronides of T2, HT2, 3-hydroxy-T2 and 3-hydroxy-HT2 by demonstrating the release of the respective aglycones from a polar metabolite fraction, assumed to represent glucuronides, upon treatment with the enzyme b-glucuronidase (reviewed by Weidner et al, 2012). More recently, LC-MS together with reference compounds has been used to identify T2-GlcA and HT2-3-GlcA in two human cell types after incubation with T2 (Weidner et al, 2012). When hepatic microsomes of rat, mouse, pig and human were incubated with T2 in the presence of uridine 5 0 -diphospho-glucuronic acid (UDPGA) and the pattern of glucuronides determined by LC-MS/MS, human microsomes exhibited a higher activity for glucuronidation than rodent or pig microsomes.…”
Section: Phase II Metabolismmentioning
confidence: 99%
“…A mixture of HT2-3-GlcA and HT2-4-GlcA was also demonstrated in the urine of female pigs dosed orally or by intravenous (i.v.) injection with T2 (Weidner et al, 2012).…”
Section: Phase II Metabolismmentioning
confidence: 99%